(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2025)
This paper studies the scientific, methodological and practical aspects of introducing simplified administrative and legal procedures to stimulate and support the export activities of small and medium-sized businesses, and further improving the infrastructural environment to expand their participation in foreign economic activity.